Chylous Ascites in a Patient with HIV/AIDS: A Late Complication of Mycobacterium avium Complex-Immune Reconstitution Inflammatory Syndrome - Imam H. Shaik; Fernando Gonzalez-Ibarra; Rumana Khan; Saira Shah; Amer K. Syed; David Lintz (Case Reports in Infectious Diseases)
Chylous ascites is very rare in HIV/AIDS and its association with Mycobacterium avium complex-immune reconstitution inflammatory syndrome (MAC-IRIS) has been rarely reported. Here, we report a case of a young African-American male who developed chylous ascites as a late sequela to immune reconstitution inflammatory syndrome while on treatment for MAC. Antiretroviral drug-naive patients who start HAART in close proximity to the diagnosis of an opportunistic infection and have a rapid decline in HIV RNA level should be monitored for development of IRIS. Although the long term prognosis is poor, early diagnosis and treatment help to improve quality of life.